Weld failures in sleeve reinforcements of pipelines - Otegui, Luis Jose (2000)
Based on fractographic, metallurgical, mechanical and fracture mechanics analyses, the causes of three failures in welded full encirclement sleeve repairs in a 24 in gas pipeline were evaluated. These failures were related to poor manufacturing procedures. The material used to build the sleeves was old and had poor transverse strength. High heat input cellulosic electrodes were used to weld the field joints, which lead to hydrogen embrittlement in the HAZ, also helped by relatively high circumferential stresses and defects of lack of fusion. A series of changes were introduced, including improvements in the in-plant fabrication and the in-field installation of the repair sleeves. A low hydrogen weld procedure with controlled penetration, NDE specifications and epoxy fillers were introduced to minimize the risk of sleevefailures and plastic collapse of the pipe